Spectral characterization of forest plantations with Landsat 8/OLI images for forest planning and management - Alba, Elisiane; Mello, Eliziane Pivotto; Marchesan, Juliana; Silva, Emanuel Araújo; Tramontina, Juliana; Pereira, Rudiney Soares (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the use of Landsat 8/OLI images to differentiate the age and estimate the total volume of Pinus elliottii, in order to determine the applicability of these data in the planning and management of forest activity. Fifty-three sampling units were installed, and dendrometric variables of 9-and-10-year-old P. elliottii commercial stands were measured. The digital numbers of the image were converted into surface reflectance and, subsequently, vegetation indices were determined. Red and nearinfrared reflectance values were used to differentiate the ages of the stands. Regression analysis of the spectral variables was used to estimate the total volume. Increase in age caused an addition in reflectance in the near-infrared band and a decrease in the red band. The general equation for estimating the total volume for P. elliottii had an R²adj of 0.67 with a Syx of 31.46 m³ ha-1. Therefore, the spectral data with medium spatial resolution from the Landsat 8/OLI satellite can be used to distinguish the growth stages of the stands and can, thus, be used in the planning and proper management of forest activity on a spatial and temporal scale